Diversity of lactic acid bacteria isolated during fermentation of indigenous cassava obtained from Sumba, East Nusa Tenggara, Indonesia - IMMANUELLA BERLIANA ELVANI HUTAJULU; PERISKILA DINA KALI KULLA; Endah Retnaningrum (Society for Indonesian Biodiversity, 2021)
Abstract. Hutajulu IBE, Kulla PDK, Retnaningrum E. 2021. Diversity of lactic acid bacteria isolated during fermentation of indigenous cassava obtained from Sumba, East Nusa Tenggara, Indonesia. Biodiversitas 22: 2561-2570. Traditional fermented food products hold a great significance in the routine diet of Indonesian inhabitants. The present study investigated the diversity of lactic acid bacteria (LAB) found in fermented indigenous cassava, ubi karet busuk, produced in Sumba, East Nusa Tenggara, Indonesia. The isolated LAB was characterized for their phenotypic, biochemical, and molecular traits, which involved 16S rRNA gene sequencing, determination of lactic acid fermentation pathway, and measurement of b-glucosidase and tannase activity in the LAB strains. During fermentation, 15 LAB strains were obtained from the cassava. Among these, 93.33% strains were found to be homofermentative, whereas 6.73% strains displayed heterofermentative traits. BLASTn and phylogenetic analysis classified 15 LAB strains into six species, namely Enterococcus faecium, Enterococcus faecalis, Enterococcus casseliflavus, Leuconostoc mesenteroides, Lactococcus lactis, and Enterococcus sp. Among these, 10 LAB strains displayed b-glucosidase activity, with highest enzyme activity of 7.13 U/mL recorded in L. lactis F14IS3. Interestingly, two of these strains also showed expression of tannase, with F6IS1 strain displaying highest enzyme activity of 38.23 U/mL. Thus, the study results highlighted the suitability of these b-glucosidase and tannase-producing LAB strains to be used as a starter in the fermentation of cassava and other substrates such as vegetables, fruits, and legumes. These strains can also be utilized in animal feed, food, and beverage industries.